163k views
5 votes
Solve x2 + 8x = 33 by completing the square. Which is the solution set of the equation? {–11, 3} {–3, 11} {–4, 4} {–7, 7}

User Lingo
by
5.7k points

2 Answers

6 votes

Answer:

{-11, 3}

Explanation:

User Afridi
by
5.8k points
5 votes

Answer:

The solution of the equation are 3 , -11

Explanation:

* Lets revise how to make the completing square

- The form of the completing square is a(x - h)² + k, where a , h , k

are constant

- The general form of the quadratic is ax² + bx + c, where a , b , c

are constant

- To change the general form to the completing square form equate

them and find the constant a , h , k

* Now lets solve the problem

∵ x² + 8x = 33 ⇒ subtract 33 from both sides

∴ x² + 8x - 33 = 0

- lets change the general form to the completing square

∴ x² + 8x - 33 = a(x - h)² + k ⇒ solve the bracket of power 2

∴ x² + 8x - 33 = a(x² - 2hx + h²) + k ⇒ multiply the bracket by a

∴ x² + 8x - 33 = ax² - 2ahx + ah² + k ⇒ compare the two sides

∵ x² = ax² ⇒ ÷ x²

∴ a = 1

∴ -2ah = 8 ⇒ substitute the value of a

∴ -2(1)h = 8 ⇒ -2h = 8 ⇒ ÷ (-2)

∴ h = -4

∵ ah² + k = -33 ⇒ substitute the value of a and h

∴ (1)(-4)² + k = -33

∴ 16 + k = -33 ⇒ subtract 16 from both sides

∴ k = -49

∴ x² + 8x - 33 = (x + 4)² - 49

* Now lets solve the completing square

∵ (x + 4)² - 49 = 0 ⇒ add 49 to both sides

∴ (x + 4)² = 49 ⇒ take square root for both sides

∴ (x + 4) = ± 7

∵ x + 4 = 7 ⇒ subtract 4 from both sides

∴ x = 3

∵ x + 4 = -7 ⇒ subtract 4 from both sides

∴ x = -11

* The solution of the equation are 3 , -11

User Wpcarro
by
5.1k points